2016
DOI: 10.5935/1981-4747.20160001
|View full text |Cite
|
Sign up to set email alerts
|

Laclau, Mouffe and Strikers Federal University Teachers: Analysis of the Effects of (Im)partiality in Media Reports

Abstract: ResumoConsiderando a importância do movimento grevista para a formação de consciência de classes, espera-se encontrar uma pluralidade de vozes presentes na construção dos significados relacionados ao movimento. Assim, recorre-se à Teoria do Discurso proposta por Laclau e Mouffe (1985) na expectativa de se responder à seguinte pergunta: como a mídia arquitetou o discurso sobre a greve de 2012 dos professores universitário federais durante os quatro meses de paralisação. Assume-se uma abordagem crítica, de corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…v. 13, n. 2, p. 43-62, 2022. The present work presents similar findings as that found in three previous articles (AMARAL et al, 2014;CASSUNDÉ;BARBOSA;MENDONÇA, 2016;ENSSLIN et al, 2015). The authors Antonio Carvalho Neto and Graça Duck, who appear among the most productive in this research, are highlighted in the article by Cassundé et al (2016) as more productive and with a more significant number of citations, respectively.…”
Section: Graph 3 -Sample Research Approachsupporting
confidence: 91%
See 1 more Smart Citation
“…v. 13, n. 2, p. 43-62, 2022. The present work presents similar findings as that found in three previous articles (AMARAL et al, 2014;CASSUNDÉ;BARBOSA;MENDONÇA, 2016;ENSSLIN et al, 2015). The authors Antonio Carvalho Neto and Graça Duck, who appear among the most productive in this research, are highlighted in the article by Cassundé et al (2016) as more productive and with a more significant number of citations, respectively.…”
Section: Graph 3 -Sample Research Approachsupporting
confidence: 91%
“…In addition to this, some studies already aimed to identify the existence of publications on outsourcing (AMARAL et al, 2014;CASSUNDÉ;BARBOSA;MENDONÇA, 2016;ENSSLIN et al, 45 2015;GUIMARÃES JUNIOR;EBERHARDT, 2020). Authors revealed that research on accounting and outsourcing are ongoing; however, there is a relatively small presence on this topic in accounting journals (AMARAL et al, 2014).…”
Section: Introductionmentioning
confidence: 99%